The professional learning of the adult-child interaction: a multi-contextual study - Novo, Rosa (2012)
An issue emerging from some research studies stresses the understanding that interaction competences depend on long, subsequent processes of reflected professional learning (Oliveira-Formosinho, 2003; Pascal e Bertram, 2003). In this study, the ecological, socio-constructivist model of supervision of final teaching practice (Oliveira-Formosinho, 2002) becomes of fundamental relevance because of its assumed need to consider child pedagogy as substantive to the construction of a new vision on practical training and on a new meaning of pedagogical supervision considered as adjectival (Oliveira-Formosinho, 2005).